Leverage, Kepemilikan Manajerial, Kinerja Lingkungan dan Nilai Perusahaan: Studi Empiris pada Perusahaan Manufaktur di Indonesia - Rismayanti, Ida Ayu Widhi; Putri, I Gusti Ayu Made Asri Dwija; Suprasto, Herkulanus Bambang (E-Jurnal Akuntansi; Vol 31 No 7 (2021), 2021)
A good company value is more than just a high level of profit achievement. The use of debt, some of the shares owned by management, and the company's performance in relation to its environment all have the potential to increase firm value. The purpose of this study is to empirically test the effect of leverage, managerial ownership, and environmental performance on firm value. The research population for this study is PROPER participating manufacturing companies that are listed on the Indonesia Stock Exchange between 2017 and 2019. Purposive sampling is a method of determining the sample. Multiple regression analysis was used as the analysis technique. According to the findings of this study, leverage, managerial ownership, and environmental performance can all increase firm value. Keywords: Leverage; Managerial Ownership; Environmental Performance; Firm Value.